Strategi Pemasaran Jasa Pendidikan melalui Pendekatan Bauran Pemasaran di SD Negeri Ciputat 01 - Talitha Gani, Azmi; Juliana Nur Fajriah, Fellisa; Munawwaroh, Zahrotul (UIN Mahmud Yunus Batusangkar, 2025)
This study aims to analyze in depth the marketing strategy for educational services at SDN Ciputat 01 in South Tangerang City through a marketing mix approach that covers seven main elements: product, price, place, promotion, people, process, and physical evidence. The research method used is a descriptive qualitative approach with data collection techniques including direct observation, in-depth interviews with various stakeholders, and documentary studies of school records and activities. The research findings indicate that although the school has not formally designed and implemented a formal and systematic marketing strategy, the elements of the marketing mix have been indirectly applied in the school's daily activities. Each element is carried out through activities focused on improving the quality of educational services, student and parent satisfaction, and the active involvement of all school components. This strategy has a positive impact on the school's image in the community, strengthens public trust, and serves as an important supporting factor in increasing the number of new applicants each year.